Penguatan Literasi Keuangan Calon Guru melalui Kolaborasi Akademik Internasional antara Universitas Negeri Jakarta dan Universiti Tun Hussein Onn Malaysia - Halim Rasyid; Etyca Rizky Yanti; Yunike Berry; Abdul Latif; Mukhibatul Hikmah; Ade Sri Mulyani; Tri Lestari; Alphieza Syam (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aims to strengthen the financial literacy of prospective teachers through an international academic collaboration between the State University of Jakarta, Indonesia, and Universiti Tun Hussein Onn Malaysia. This program is designed to improve participants' understanding of personal financial management and build awareness of the importance of financial literacy as a relevant competency for prospective educators. The activity is implemented with a participatory educational approach through interactive lectures, group discussions, case-based learning, financial planning simulations, and reflection sessions. The main materials include basic concepts of financial literacy, budgeting, saving behavior, simple investment concepts, digital financial services, and financial risk management. Evaluation is carried out through participant engagement, responses in discussions, and reflective feedback after the activity. The results of the activity indicate that participants have increased awareness of the importance of wise personal financial management, especially in distinguishing needs from wants, preparing a simple budget, and understanding risks in financial decision-making.